2021
DOI: 10.3389/fpsyg.2021.655884
|View full text |Cite
|
Sign up to set email alerts
|

EEG Signal Diversity Varies With Sleep Stage and Aspects of Dream Experience

Abstract: Several theories link consciousness to complex cortical dynamics, as suggested by comparison of brain signal diversity between conscious states and states where consciousness is lost or reduced. In particular, Lempel-Ziv complexity, amplitude coalition entropy and synchrony coalition entropy distinguish wakefulness and REM sleep from deep sleep and anesthesia, and are elevated in psychedelic states, reported to increase the range and vividness of conscious contents. Some studies have even found correlations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 66 publications
3
22
1
Order By: Relevance
“…We found reduced power of EEG theta oscillations during the effects of the psilocybin microdose, heralding the larger broadband reductions observed for higher doses [ 49 ]. However, the analysis of Lempel-Ziv complexity failed to reveal differences between conditions, suggesting that increased signal entropy could constitute a specific signature of the altered consciousness elicited by psychedelics or other non-pharmacological mechanisms [ 63 65 ]. Reduced vigilance is a potential non-pharmacological mechanism underlying the observed changes in theta power.…”
Section: Discussionmentioning
confidence: 99%
“…We found reduced power of EEG theta oscillations during the effects of the psilocybin microdose, heralding the larger broadband reductions observed for higher doses [ 49 ]. However, the analysis of Lempel-Ziv complexity failed to reveal differences between conditions, suggesting that increased signal entropy could constitute a specific signature of the altered consciousness elicited by psychedelics or other non-pharmacological mechanisms [ 63 65 ]. Reduced vigilance is a potential non-pharmacological mechanism underlying the observed changes in theta power.…”
Section: Discussionmentioning
confidence: 99%
“…The result of a study showed that signal diversity of scalp EEG in healthy volunteers changed significantly with sleep stage, and was progressively reduced with deeper stages of non-REM sleep. Signal diversity decreased with sleep depth but was not significantly different between dreaming and non-dreaming stages [26]. Siddiqui et al reported that for the Alpha activity, the normalized power for insomnia cases the range is low (0.006 -0.02) while the normalize power for normal cases is in the range of 0.04 -0.12 which is high.…”
Section: Discussionmentioning
confidence: 96%
“…Several previous studies investigated the EEG of DoC patients in resting-state conditions with entropic measures to study signal complexity and its significance [3,[14][15][16][17][18] assuming brain activity can manifest under resting conditions, without needing specific types of stimuli protocols [19]. Specifically, the entropy ACE or SCE measures, which we applied, were previously validated in determining the "consciousness" changes in case of anesthesia [11], drug-induced psychedelic state [20], or sleep [21,22] but not, to our knowledge, to patients with chronic DoCs. We found that all the three applied entropy measures had a similar trend, but ACE values more often returned significant differences.…”
Section: Discussionmentioning
confidence: 99%